Different stretching methods do not affect maximal force and neuromuscular response in young soccer players - Oliveira, L. P.; Santiago, P. R.P.; Manechini, J. P.V.; Vieira, L. H.P. [UNESP]; Aquino, R.; Kalva Filho, C. A. [UNESP]; Andrade, V. L.; Puggina, E. F. (Elsevier, 2023)
Objectives: The aim of the present study was to compare the acute effects of different stretching methods on maximal force and neuromuscular responses in young soccer players. Equipment and methods: Twelve players (17.7 ± 0.9 years) were randomly subjected to active, ballistic, passive, and proprioceptive neuromuscular facilitation stretching methods, in addition to a control condition. Before and after 3 sets comprising 30 s stretching intervention, the range of motion, peak force, superimposed twitch, potentiated twitch, percentage of voluntary activation, and root mean square of the electromyography signal normalized by the maximal wave were assessed. Results: The stretching modalities effectively improved the range of motion (1.71 to 2.46 cm; P < 0.05). On the other hand, no independent (i.e., test time, condition) and interactive (i.e., test time and condition) effects were found on maximal force and neuromuscular parameters. Conclusion: Active, ballistic, passive and proprioceptive neuromuscular facilitation stretching did not negatively affect the subsequent maximal force and muscle activation, but enhanced soccer players’ range of motion. The results suggest that physical trainers and athletes could use these stretching modalities to improve flexibility without subsequent adverse effects on maximal force.
Les différentes méthodes d’étirement n'affectent pas la force maximale et la réponse neuromusculaire chez les jeunes joueurs de football
Keywords: Muscle strength; Physical performance; Range of motion; Team sports